One-Year Outcomes of 1 Dose versus 3 Loading Doses Followed by Pro Re Nata Regimen Using Ranibizumab for Neovascular Age-Related Macular Degeneration: The ARTIS Trial - Fenghua Wang; Yuanzhi Yuan; Ling Wang; Xiaofeng Ye; Jingke Zhao; Mengxi Shen; Qi Zhang; Ding Xu; Guoyou Qin; Wei Zhang; Fei Yuan; Qing Chang; et al. (Journal of Ophthalmology)
Purpose. To compare the functional and anatomical outcomes of one dose and three loading doses followed by the pro re nata (PRN) regimen in Chinese neovascular age-related macular degeneration (nvAMD) (including polypoidal choroidal vasculopathy (PCV)) patients. Methods. In this multicenter, prospective, open-label, controlled, 12-month study (ClinicalTrials.gov: NCT02810808), patients were randomized (1 : 1) to 1 dose + PRN (PRN group) or 3 loading doses + PRN (LD group) using intravitreal ranibizumab treatment. Best-corrected visual acuity (BCVA) and central retinal thickness (CRT) were evaluated. The main outcome was the change in BCVA. The noninferiority limit was 5 letters. Results. Forty-five patients in the PRN group and 49 patients in the LD group finished 12-month follow-up. Each group included 4 PCV patients. The mean change in BCVA from baseline was 7.8 letters in the PRN group, compared with 10.9 letters in the LD group (P=0.344). There were no significant differences between two groups in the mean change of CRT (−159.3 μm vs. −120.5 μm) at month 12. The mean number of injections during the 12-month follow-up was 6.0 in the PRN group and 6.8 in the LD group. The proportion of patients who gained an improvement in visual acuity by 15 or more letters was 28.9% in the PRN group and 44.9% in the LD group (P=0.066). Conclusion. One dose + PRN showed noninferior visual gains than 3 loading doses + PRN regimen using ranibizumab in Chinese nvAMD and PCV patients. Number of injections in the PRN group was similar as that in the LD group but remained a potential risk of vision instability during one-year follow-up using OCT-guided retreatment criteria. This trial is registered with NCT02810808.